Infiltrasi Pemikiran Feminisme Liberal dalam Kompilasi Hukum Islam - Yusra, Hannilfi (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Islam adheres to a patriarchal culture, where men are held higher than women, as is the deepest in the word of Allah. Meanwhile, feminists oppose and reject the patriarchal system because it is considered that women are only capable of performing reproductive functions such as; giving birth, raising children and carrying out household responsibilities As for liberal feminism, it emphasizes that women and men are created equal, have the same rights and must be given the same opportunities. Liberal feminist thought is known for advocating for gender equality, individual freedom, and rejection of discrimination against women in all its forms. In the context of Liberal Feminism, a review of the Compilation of Islamic Law can provide a deeper understanding of how Islamic law is applied to women and how issues of gender equality and the role of women are addressed in the law. This research aims to better understand this liberal feminism mind in the compilation of Islamic law. The method used in this study is qualitative descriptive using literature review as the source of data. The result of this study is that in the compilation of Islamic law, there are actually several articles that support feminist thought, such as article 32 paragraph 2 of the KHI regarding property and several other articles. The conclusion of this study is that there is a compatibility between the rules in the KHI and the principles of liberal feminism as evidence that the KHI actually accepts the ideology of liberal feminism.